2008
DOI: 10.1016/j.bbrc.2007.11.104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cathepsins B and L inhibition on postischemic protein alterations in the brain

Abstract: The effects of selective inhibition of cathepsins B and L on postischemic protein alterations in the brain were investigated in a rat model of middle cerebral artery occlusion (MCAO). Cathepsin B activity increased predominantly in the subcortical region of the ischemic hemisphere where the levels of collapsing mediator response protein 2, heat shock cognate 70 kDa protein, 60 kDa heat shock protein, protein disulfide isomerase A3 and albumin, were found to be significantly elevated. Postischemic treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
1
17
0
2
Order By: Relevance
“…However, inhibitors of cathepsin B (and L) have been shown to have a neuroprotective effect in animal models of ischemia, preventing apoptosis [48; 49; 50; 51; 52] and prolonged treatment of animals with cathepsin inhibitors do not produce any significant neurological toxic effects [19; 20]. The deleterious effects of protease loss in the cathepsin B and L double knockout mice are primarily due to early post-natal effects on rapidly proliferating neuronal cells whereas non-proliferating cells of the central nervous system of adult mice appears to be refractory to protease inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…However, inhibitors of cathepsin B (and L) have been shown to have a neuroprotective effect in animal models of ischemia, preventing apoptosis [48; 49; 50; 51; 52] and prolonged treatment of animals with cathepsin inhibitors do not produce any significant neurological toxic effects [19; 20]. The deleterious effects of protease loss in the cathepsin B and L double knockout mice are primarily due to early post-natal effects on rapidly proliferating neuronal cells whereas non-proliferating cells of the central nervous system of adult mice appears to be refractory to protease inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with cathepsin B inhibitors, including stefin A, epoxysuccinyl peptides and cysteine protease inhibitor 1, reduced ischemia-induced neuron death. [27][28][29][30] However, in other pathological conditions, autophagy is reported to be associated with neuroprotection. [31][32][33] Thus, the role of autophagy in cell death and survival in cerebral ischemia remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…35 In addition, Seyfried et al have shown that neuronal cathepsin B undergoes increased expression and activation within 2 hours of reperfusion after a 2-hour MCA occlusion and may be a mechanism contributing to neuronal cell death and that intraventricular infusion of stefin A, an inhibitor of cathepsin B, significantly reduces cerebral infarct volume in rats. Recently, Angali et al, 2 have demonstrated that a posttreatment with cysteine protease inhibitor (CP-1) reduced infract volume, neurological deficits and cathepsin B activity in a rat model of focal ischemia.…”
Section: Participation Of Lysosomal Proteases In Neuron Death After Gmentioning
confidence: 99%